Salicylic Acid Alleviates the Adverse Effects of Salt Stress on Dianthus superbus (Caryophyllaceae) by Activating Photosynthesis, Protecting Morphological Structure, and Enhancing the Antioxidant System - Ma, Xiaohua; Zheng, Jian; Zhang, Xule; Hu, Qingdi; Qian, Renjuan (Frontiers in Plant Science, 2017)
Salt stress critically affects the physiological processes and morphological structure of plants, resulting in reduced plant growth. Salicylic acid (SA) is an important signal molecule that mitigates the adverse effects of salt stress on plants. Large pink Dianthus superbus L. (Caryophyllaceae) usually exhibit salt-tolerant traits under natural conditions. To further clarify the salt-tolerance level of D. superbus and the regulating mechanism of exogenous SA on the growth of D. superbus under different salt stresses, we conducted a pot experiment to examine the biomass, photosynthetic parameters, stomatal structure, chloroplast ultrastructure, reactive oxygen species (ROS) concentrations, and antioxidant activities of D. superbus young shoots under 0.3%, 0.6% and 0.9% NaCl conditions, with and without 0.5 mM SA. D. superbus exhibited reduced growth rate, decreased net photosynthetic rate (Pn), increased relative electric conductivity (REC) and malondialdehyde (MDA) contents, and poorly developed stomata and chloroplasts under 0.6% and 0.9% salt stress. However, exogenously SA effectively improved the growth, photosynthesis, antioxidant enzyme activity and stoma and chloroplast development of D. superbus. However, when the plants were grown under severe salt stress (0.9% NaCl condition), there was no significant difference in the plant growth and physiological responses between SA-treated and non-SA-treated plants. Therefore, our research suggests that exogenous SA can effectively counteract the adverse effect of moderate salt stress on D. superbus growth and development.